Post-traumatic stress in patients with injury-related chronic pain participating in a multimodal pain rehabilitation program - Stålnacke, Britt-Marie (Dove Medical Press, 2010)
AIM: To investigate post-traumatic stress, pain intensity, depression, and anxiety in patients with injury-related chronic pain before and after participating in multimodal pain rehabilitation. METHODS: Twenty-eight patients, 21 women and seven men, who participated in the multimodal rehabilitation programs (special whiplash program for whiplash injuries within 1.5 years after the trauma or ordinary program) answered a set of questionnaires to assess post-traumatic stress (Impact of Event Scale [IES], pain intensity [Visual Analogue Scale (VAS)], depression, and anxiety (Hospital Anxiety and Depression Scale [HAD] before and after the programs. RESULTS: Both pain intensity and post-traumatic stress decreased significantly after the rehabilitation programs in comparison with before (VAS: 57.8 ± 21.6 vs. 67.5 ± 21.9; P = 0.009, IES total score 21.8 ± 13.2 vs. 29.5 ± 12.9; P < 0.001). Patients younger than 40 years reported a statistically higher level of post-traumatic stress compared with patients older than 40 years both before (P = 0.037) and after rehabilitation (P = 0.023). No statistically significant differences were found on the HAD scores. CONCLUSION: The multimodal rehabilitation programs were effective in reducing both pain intensity and post-traumatic stress. The experience of higher levels of post-traumatic stress in younger persons has to be taken into account when managing patients with injury-related chronic pain.